Participatory democracy and civil society – transforming societal decision making in the information age - Keskinen, Auli (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 1998)
Various points of view to the current global social transition period and the coming of the information age, both of which are characterized by an unprecedented global telecommunications and information networks explosion will be discussed. Our position is that the rapid diffusion of computers and connected networks of electronic means, the information and communications technology (ICT) will have even more profound impact than before on various social phenomena such as work, entertainment, business, education and, most important of all, democracy - how it is understood, exercised and developed. What is ready to be born, then, is "teledemocracy" - a new form of direct democracy promoted by the ICT and Information Networks.